2022
DOI: 10.1002/1878-0261.13299
|View full text |Cite
|
Sign up to set email alerts
|

Tieing together loose ends: telomere instability in cancer and aging

Abstract: Telomere maintenance is essential for maintaining genome integrity in both normal and cancer cells. Without functional telomeres, chromosomes lose their protective structure and undergo fusion and breakage events that drive further genome instability, including cell arrest or death. One means by which this loss can be overcome in stem cells and cancer cells is via re‐addition of G‐rich telomeric repeats by the telomerase reverse transcriptase (TERT). During aging of somatic tissues, however, insufficient telom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 230 publications
(253 reference statements)
0
7
0
Order By: Relevance
“…Previous studies stated that the telomeres in cancer patients are shorter but sta-ble when compared to healthy individuals. 18,20,21 Also, a study analysing telomere length in pleural effusion cells reported shorter telomeres in 12 MM patients compared to 35 cases with non-neoplastic disease. 23 Interestingly, older patients with MM had longer telomeres than younger patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies stated that the telomeres in cancer patients are shorter but sta-ble when compared to healthy individuals. 18,20,21 Also, a study analysing telomere length in pleural effusion cells reported shorter telomeres in 12 MM patients compared to 35 cases with non-neoplastic disease. 23 Interestingly, older patients with MM had longer telomeres than younger patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] The regulation of the expression of the human telomerase reverse transcriptase (hTERT) subunit of telomerase occurs predominantly at the transcriptional level. [19][20][21] Numerous single nucleotide polymorphisms (SNP) in the hTERT gene may also have an impact on telomerase expression levels and activity, and may thus play a role in the risk of carcenogenesis, as well as the prognosis and survival of cancer patients. 18,19,22 Telomere length is influenced by cellular senescence, chronic inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, dysfunctional telomeres, reminiscent of DNA double‐strand breaks, can also promote genome DNA recombination events, genome instability, and cancer [60]. Lea Harrington and colleagues discuss this dual role of telomeres in aging and cancer, including as targets for therapeutic interventions and potential cross‐over of healthy aging interventions and cancer prevention [61].…”
Section: Other Potential Causes Of Age‐associated Cancermentioning
confidence: 99%
“…Mutations in chromosome capping proteins or critical shortening of telomeric DNA tracts can lead to an increased incidence of end-to-end chromosome fusions and genome aberrations (Borges et al 2022;Song et al 2008). To check if telomere integrity is compromised in an3 and oli mutants, we performed cytogenetic analysis of mitotically dividing cells in pistils.…”
mentioning
confidence: 99%